(untitled) (Bangladesh Journal of Microbiology, 2019)
In Bangladesh, food sold at local markets are usually not kept under hygienic conditions leading to contamination with different microorganisms and deterioration of food quality. This study was carried out to examine the microbial quality of prawns sold at local markets. Prawn samples collected from different markets were assessed for their bacteriological quality using the multiple tube fermentation technique to determine coliform count using the most probable number method in Brilliant Green Lactose Broth (BGLB) media. Positive tubes of the presumptive test were further cultured on Eosine Methylene Blue(EMB) and Mac Conkey agar media. The organisms isolated were further characterized using biochemical tests. Out of the 65 samples, 47 (72.3%) showed positive results in all 3 tubes of dilution series using inoculum quantities of 1, 0.1 and 0.01 g.Among 65 samples 57 samples that contained at least one positive in each dilution series were further re-identified with biochemical tests.This study showed 56.14%isolates were Escherichia coli which conformed to expected biochemical reactions, formed round, small,elevated colonies with pink pigmentation on Mac Conkey agar media and round, small colonies with metallic green sheen pigmentation on EMB agar media. Other bacteria which presumptively appeared to be enterics and were isolated from BGLB were identified as Klebsiellapneumoniae(29.82%),Staphylococcus aureus(8.7%), Enterobacter aeroginosa(3.5%) and Salmonellatyphimurium (1.75%).Presumptive identification of E. coli in prawn in order to determine fecal contamination was able to identify ¾ of BGLB tubes with actual occurrence of E. coli. From this study it has been found that 97.14% bacteria were sensitive to Co-Trimoxazole, compared to other antibiotics used in this test whereas only 37.14% bacteria were sensitive to nitrofurantoin. This study also highlighted the fact that prawns act as a major source of E. coli which indicates possible fecal contamination as well as presence of potentially pathogenic E. coli and these bacteria are resistant at a great percentage to almost all of these antibiotics used in this study. Prawns must therefore be cooked adequately before consumption. Bangladesh J Microbiol, Volume 35 Number 1 June 2018, pp 13-16